Environmental determinants of the distribution of the Cabrera vole (Microtus cabrerae) in Portugal: Implications for conservation - Mira, António (2009)
The main aim of this study was to update the distribution of the Cabrera vole (Microtus cabrerae) in Portugal in order to determine regions of suitable environmental conditions and to assess potential occurrence areas, as a first step towards a conservation strategy for the species. Data on the distribution of the species was derived from barn owl pellet samples. Climatic, topographic and soil descriptors were selected and logistic regression was used to model the species distribution. The effort in data collection resulted in the enlargement of the previously known distribution of M. cabrerae. Two logistic models were developed, one environmental and one autologistic, integrating variation due to spatial autocorrelation. The results showed that the species are more likely to occur over the most central region of Portugal, extending its range to the north-eastern side and to the southwest. The preferred areas of occurrence are characterized by medium rainfall values (between 600 and 1200 mm), low to medium humidity values (lower than 85%) and acid to neutral soils (pH between 3 and 7). Species probability of occurrence is discussed in terms of paleontological data and geographical barriers. Potential distribution maps suggest a fragmentation of the overall national population and allowed the identification of three major areas of high probability of occurrence: northeast, center and southwest. As most of these areas are outside Classified Areas Network, models obtained may be regarded as valuable tools in conservation planning.